The degree of competition in the Malaysian dual banking industry - Nafisah Mohammed,; Junaina Muhammad,; Abdul Ghafar Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to evaluate the degree of competition in the Malaysian dual banking industry to address the question of whether Islamic banks are able to cope with competition from the well-established conventional banks. The Panzar-Rosse (PR) method has been used to measure the degree of competition in Islamic compared with conventional banking market over the period of 1997-2016. Present study uses static panel data estimation to estimate the developed models. Results from the H-statistics values using total income show that level of competition in the Islamic banking market is more intense than conventional banking market. Hence, providing evidence that Islamic banks are able to compete with conventional banks that have long history of establishment. The H-statistic values using total interest income also indicate the same result, hence supporting the robustness of these results. The findings also show the effectiveness of policy changes adopted by Bank Negara Malaysia in order to increase level of competition in both banking markets. Hence, knowledge on this issue is important to the policy makers for them to formulate new policy regarding banking competition.